2015
DOI: 10.1002/uog.14651
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of prenatal ultrasound in detecting jejunal and ileal atresia: systematic review and meta‐analysis

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 33 publications
7
39
1
Order By: Relevance
“…24,33,41 In a recent systematic review, our group explored the role of prenatal ultrasound in detecting non-duodenal small bowel atresia in otherwise normal fetuses. 47 We found that ultrasound had a poor accuracy in detecting small bowel atresia either using bowel dilatation or polyhydramnios. In gastroschisis, we could not define the accuracy of prenatal ultrasound in detecting BA but we could calculate a four times increased risk when IABD was present.…”
Section: Comparison With Other Systematic Reviewsmentioning
confidence: 76%
“…24,33,41 In a recent systematic review, our group explored the role of prenatal ultrasound in detecting non-duodenal small bowel atresia in otherwise normal fetuses. 47 We found that ultrasound had a poor accuracy in detecting small bowel atresia either using bowel dilatation or polyhydramnios. In gastroschisis, we could not define the accuracy of prenatal ultrasound in detecting BA but we could calculate a four times increased risk when IABD was present.…”
Section: Comparison With Other Systematic Reviewsmentioning
confidence: 76%
“…There have been numerous reports on the antenatal diagnosis of intestinal atresia using two‐dimensional (2D) sonography. HDlive and HDlive inversion mode are useful in the prenatal differentiation of meconium peritonitis from intestinal atresia.…”
mentioning
confidence: 99%
“…This is further supported by reports regarding the superiority of foetal MRI in overcoming the limitations associated with sonography, such as operator dependence, inherent inferior image contrast, patient factors such as obesity and small field of view, and non-specific US findings which may relate to transient normal variants [20-22]. The detection of jejunal and ileal atresia with US alone is low with detection rates of 66.3 and 25.9%, respectively, and MRI has been shown to improve detection of small and large bowel obstructions, malrotation, and perforations resulting in meconium peritonitis or pseudocyst [20-23]. Although jejunoileal atresia is associated with a good survival rate, surgical therapy should be expedited; hence, cases with prenatal suspicions warrant careful postnatal assessment with plain abdominal radiograph or enema studies, even if the prenatal ultrasonographic differences have resolved prior to delivery [24].…”
Section: Discussionmentioning
confidence: 99%